2019
DOI: 10.3390/polym11121917
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose in Ionic Liquids and Alkaline Solutions: Advances in the Mechanisms of Biopolymer Dissolution and Regeneration

Abstract: This review is focused on assessment of solvents for cellulose dissolution and the mechanism of regeneration of the dissolved biopolymer. The solvents of interest are imidazole-based ionic liquids, quaternary ammonium electrolytes, salts of super-bases, and their binary mixtures with molecular solvents. We briefly discuss the mechanism of cellulose dissolution and address the strategies for assessing solvent efficiency, as inferred from its physico-chemical properties. In addition to the favorable effect of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 127 publications
(178 reference statements)
2
34
0
1
Order By: Relevance
“…For instance, for 1‐butyl‐3‐methylimidazolium acetate the chemical shift of the C 6 carbon occurred at δ H /δ C 1.73/31.3 in both samples. This also agrees with El Seoud et al., who reported stronger changes in chemical shifts of C 2 due to the increased hydrogen bonding with the cellobiose …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, for 1‐butyl‐3‐methylimidazolium acetate the chemical shift of the C 6 carbon occurred at δ H /δ C 1.73/31.3 in both samples. This also agrees with El Seoud et al., who reported stronger changes in chemical shifts of C 2 due to the increased hydrogen bonding with the cellobiose …”
Section: Resultssupporting
confidence: 92%
“…El Seoud et al. also reported that the chemical shift of an ionic liquid containing an acetate anion [1‐( n ‐butyl)imizaolium acetate] was influenced by the presence of cellobiose . Further, the C 2 of 1‐butyl‐3‐methylimidazolium acetate had a chemical shift at δ H /δ C 10.43/138.0, but when combined with the pretreated biomass the chemical shift was located at δ H /δ C 10.21/137.8, a difference of δ H /δ C 0.22/0.2.…”
Section: Resultsmentioning
confidence: 99%
“…We assumed that ionic liquid based solvents that were applied for the dissolution of cellulose [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] can also be applied for the dissolution of cellulose- O -phosphates.…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, therefore, WB is much more sensitive to changes in the experimental variables than other solvatochromic probes that are used to calculate specific Cel-solvent interactions. Note that empirical solvent polarity is related to the parameters that describe the specific solute–solvent interactions by Equation (5) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]: E T (probe) = E T (probe) 0 + a SA + b SB + d SD + p SP where SB is as defined before; SA , SD , and SP refer to Lewis acidity, dipolarity, and polarizability, respectively. That is, the dependence of E T (probe) on the experimental variables reflects collectively the dependence (on the same variables) of hydrogen bonding (as given by SA and SB ) and the hydrophobic interactions (related to SP ).…”
Section: Resultsmentioning
confidence: 99%